Histamine H3 Receptor Ligands in the Group of (Homo)piperazine Derivatives - Szczepanska, Katarzyna; Kuder, Kamil; Kiec-Kononowicz, Katarzyna (Current Medicinal Chemistry, 2018)
Since its discovery in 1983, followed by gene cloning in 1999, the histamine H3 receptor served as an outstanding target for drug discovery. The wide spectrum of possible therapeutic implications makes H3R's one of the most researched areas in the vast GPCR ligands field - started from imidazole containing ligands, through various successful imidazole replacements, with recent introduction of Wakix® to pharmaceutical market. One such replacement is piperazine moiety, a significant versatile scaffold in rational drug design for most of the GPCR ligands. Therefore, herein, we review ligands built on piperazine, as well as its seven membered analogue azepine, that target H3R's and their potential therapeutical applications, in order to elucidate the current state of the art in this vast field. Due to a high level of structural divergence among compounds described herein, we decided to divide them into groups, where the key division element was the position of nitrogen basicity decreasing moieties in (homo)piperazine ring. Paying attention to a number of published structures and their overall high biological activity, one can realize that the (homo)piperazine scaffold bids a versatile template also for histamine H3 receptor ligands. With two possible substitution sites and therefore a number of possible structural combinations, piperazine derivatives stand as one of the largest group of high importance among H3R ligands.
Keywords: Histamine H3 receptor